Sistema de seguimiento por imágenes asistido por GNSS-GPS: TV Tracker - García Bravo, Santiago; Curetti, María; Arri, Gabriela; Pucheta, Julián; Mathé, Ladislao (2022)
Fil: García Bravo, Santiago. Instituto Universitario Aeronáutico; Argentina.